2016
DOI: 10.1139/as-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Applications of local floras for floristic subdivision and monitoring vascular plant diversity in the Russian Arctic

Abstract: The local flora method has been used by Russian botanists for studying vast wilderness areas. The method strives to determine the total flora within a certain limited area and provides comparable data for spatial comparisons between different locations and temporal comparisons at the same location. Complete vascular plant diversity was sampled in 240 localities with an area between 100 and 300 km2 each throughout the Russian Arctic. These data were incorporated in a specially developed Integrated Botanical Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…The "local flora method" elaborated by Tolmatchev (1931Tolmatchev ( , 1974 and his disciples (see Rebristaya 1977, Yurtsev 1975, 1982, Yurtsev et Semkin 1980 is broadly used in Russia for the studies focused on plant biodiversity, especially in the vast Arctic wilderness areas. Local flora (LF) theory was recently presented for international readers (Khitun et al 2016). The LF method strives to determine the total vascular plant flora in a specific locality by thorough inspection of all of all habitat types found in the locality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "local flora method" elaborated by Tolmatchev (1931Tolmatchev ( , 1974 and his disciples (see Rebristaya 1977, Yurtsev 1975, 1982, Yurtsev et Semkin 1980 is broadly used in Russia for the studies focused on plant biodiversity, especially in the vast Arctic wilderness areas. Local flora (LF) theory was recently presented for international readers (Khitun et al 2016). The LF method strives to determine the total vascular plant flora in a specific locality by thorough inspection of all of all habitat types found in the locality.…”
Section: Introductionmentioning
confidence: 99%
“…It allows find many rare and small in size species, which otherwise could be missed. Empirically it has been shown that the representative area for such study in lowland Arctic is approximately 100 km 2 (Khitun et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that trend in tree radial growth depended on not only temperature but also precipitation regimes even in Arctic region. In recent decades, young larch trees and species from adjacent bioclimatic regions have been reported in this area (Khitun et al, 2016), indicating that it might be possible to change the ecosystem structure at the species level, and also the ecosystem function at the landscape level. The larch tree and shrub classes had close to zero CH 4 sink in this study, suggesting the weak ability of forests in the boundary ecosystem to oxidise CH 4 compared to a mature boreal forest.…”
Section: Factors Controlling Local Ch 4 Emissions In the Taiga-tundramentioning
confidence: 99%
“…the middle of the Indigirka lowland) is sparsely covered by larch trees (a taiga-tundra boundary ecosystem), which grow on elevated mounds because of low soil moisture and nitrogen uptake (Liang et al, 2014). In recent years, an increasing number of invasive (expanded) species from more southern areas have been reported (Khitun et al, 2016), likely owing to the rising temperatures. Thus, the very specific nature of this environment, combined with continuous permafrost, the tree distribution limit and river lowlands, renders the ecosystems of this region potentially vulnerable to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…It is best to conduct vegetation surveys in conjunction with taxonomists who can devote the time necessary to make professional herbarium voucher collections and produce floristic surveys that include complete vascular-plant, bryophyte, and lichen species lists from a full suite of habitat types at each station. A standardized method of making local floras has been applied to approximately 500 locations in Russia (Tolmachev 1931, Yurtsev et al 2004, Balandin 2008, Khitun et al 2016. The Russian approach to making local floras should be considered and modified if necessary for other Arctic countries.…”
Section: Local Florasmentioning
confidence: 99%